Reliability of the run of eight test in athletes after knee surgery - Nitzsche, N.; Hamacher, D. (Sports Orthopaedics and Traumatology, 2025)
Summary Background: Knee injuries and surgery result often in neuromuscular and functional deficits in Athletes. These motor deficits can increase the risk of re-injury and make it more difficult to return to sport. The "run of eight" is a practical test for running performance, which should be reliably recorded. The aim of this study was to demonstrate the reliability and variability of the run of eight (Ro8) in athletes who have undergone a knee surgery. Material and methods: 17 Athletes (age 32.8 ± 1.5 years; BMI 25.6 ± 5.3 kgm-2) after ACL surgery were tested for their running performance using the Ro8 test. Running performance was assessed on two different days with a duration of one minute and the number of laps run was recorded. The test-retest reliability was determined using Pearson correlation coefficients. The variability was calculated using the RMSE and Bland-Altman plots. The Pearson correlation coefficient was used to determine the correlations between the performance and the function values. Results: The correlation coefficient of the Ro8 of T1 and T2 was r = 0.86 (p < 0.001). The RMSE between T1 and T2 was 0.5 laps with a critical difference using LoA = 1.4 laps. There was a correlation coefficient between Lysholm score and Ro8 of r = 0.46 (p > 0.05) and KOS and Ro8 of r = 0.68 (p < 0.003). Furthermore, there was a moderate correlation between the average number of laps of T1 and T2 and the time after surgery (r = 0.55; p < 0.05). Conclusion: The Ro8 to determine running performance in athletes following knee joint surgery due to injury is suitable for testing training-related adaptations in performance and function during rehabilitation due to the reliability demonstrated in this study. Zusammenfassung Hintergrund: Sportler zeigen infolge von Verletzungen und Operation am Kniegelenk neuromuskuläre und funktionelle Defizite. Diese motorischen Defizite können das Risiko einer erneuten Verletzung erhöhen und die Rückkehr zum Sport erschweren. Der Achterlauf testet praxisnah die Laufleistung, welche zuverlässig erfasst werden sollte. Ziel der Studie war es, die Reliabilität und Variabilität des Achterlaufs bei Sportlern nach einer Knieoperation zu überprüfen. Material und Methoden: 17 Sportler (Alter 32,8 ± 1,5 Jahre; BMI 25,6 ± 5,3 kgm-2) wurden nach einer Rekonstruktion des vorderen Kreuzbandes mit dem Achterlauf auf ihre Laufleistung getestet. Die Laufleistung wurde an zwei verschiedenen Tagen mit einer Dauer von einer Minute durchgeführt und dabei die Anzahl der gelaufenen Runden erfasst. Die Test-Retest-Reliabilität wurde mittels Pearson-korrelation bestimmt. Die Berechnung der Variabilität erfolgte durch den RMSE sowie Bland-Altman Plots. Zusammenhänge zwischen der Laufleistung und funktionellen Scores (Lysholm Score, Knee Outcome Score) wurden anhand von Pearson-Korrelations-Koeffizienten geprüft. Ergebnisse: Der Korrelationskoeffizient des Ro8 betrug r = 0,86 (p < 0,001). Der RMSE zwischen T1 und T2 betrug 0,5 Runden mit einer kritischen Differenz von LoA = 1,4 Runden. Es bestand ein Korrelationskoeffizient zwischen Lysholm-Score und Ro8 von r = 0,46 (p > 0,05) und zwischen KOS und Ro8 von r = 0,68 (p < 0,003). Es ergab sich eine mittlere Korrelation zwischen der durchschnittlichen Anzahl der Runden und der Zeit nach der Operation (r = 0,55; p < 0,05). Schlussfolgerung: Der Achterlauf zur Bestimmung der Laufleistung bei Athleten nach verletzungsbedingten Operationen am Kniegelenk ist aufgrund der hier festgestellten Reliabilität geeignet trainingsbedingte Anpassungen der Leistung und Funktion während der Rehabilitation zu prüfen. Autorreferat